Efficacy and safety of thrombopoietin receptor agonists in children with chronic immune thrombocytopenic purpura: meta-analysis. (3rd October 2019) - Tumaini Massaro, Joyce; Chen, Yanhui; Ke, Zhongling
Abstract: Immune thrombocytopenic purpura (ITP) is an autoimmune disorder presenting with low platelet count <100 × 10 9 /L. The condition affects both adults and children. Thrombopoietin receptor agonists (TPO-RAs) are second-line of therapy that includes Romiplostim and Eltrombopag, which stimulate the production of normally functioning platelets. Although the biological effect of these drugs is well established, there has not been a meta-analysis in children. To estimate the efficacy and safety of Romiplostim and Eltrombopag, we performed a systematic review and meta-analysis in children with chronic ITP. Systematic literature search was conducted in the following database: PubMed, EMBASE, and Cochrane Central Register of Controlled Trials (CENTRAL). Review Manager 5.3 for Windows was used to analyze the data. Five randomized controlled trials with total of 261 pediatric patients from 1–17 years of age were included. The efficacy and safety analysis showed TPO-RA groups were superior over placebo, and there was no difference in adverse event occurrence between TPO-RA (Romiplostim and Eltrombopag) and placebo groups. The efficacy and safety of Eltrombopag did not differ significantly from those of Romiplostim. Both drugs were effective in treatment of children with chronic ITP. Our findings extend the currently available data on ITP treatment and is helpful for pediatric health providers and for the design of future clinical trials.